Magi : the labyrinth of magic. 29 - Otaka, Shinobu; Werry, John (Translator) (VIZ Media, LLC, 2018)
"The internal strife within the Kou Empire comes to a resolution, and a great price must be paid for peace. Once-powerful nations find themselves humbled, and the world is changing once again. Elsewhere, the long-absent Alibaba and Judar continue their strange journey with the Primeval Dragon, and learn a shocking truth about Sinbad"--Amazon.com